Estimating minimal important differences for several scales assessing function and quality of life in patients with attention-deficit/hyperactivity disorder. (18th August 2016) - Hodgkins, Paul; Lloyd, Andrew; Erder, M. Haim; Setyawan, Juliana; Weiss, Margaret D.; Sasané, Rahul; Nafees, Beenish
Abstract : Objective: Defining minimal important difference (MID) is critical to interpreting patient-reported outcomes data and treatment efficacy in clinical trials. This study estimates the MID for the Weiss Functional Impairment Rating Scale–Parent Report (WFIRS-P) and the Child Health and Illness Profile–Parent Report (CHIP-CE-PRF76) among parents of young people with attention-deficit/hyperactivity disorder (ADHD) in the UK. Methods: Parents of children (6–12 years; n=100) and adolescents (13–17 years; n=117) with ADHD completed a socio-demographic form, the CHIP-CE-PRF76, the WFIRS-P, and the Pediatric Quality of Life scale at baseline and 4 weeks later. At follow-up, a subset of parents completed anchor questions measuring change in the child/adolescent from baseline. MIDs were estimated using anchor-based and distribution-based methods, and separately for children and adolescents. Results: The MID estimates for overall change in the WFIRS-P total score ranged from 11.31 (standard error of measurement) to 13.47 (anchor) for the total sample. The range of MID estimates for the CHIP-CE-PRF76 varied by domain: 6.80–7.41 (satisfaction), 6.18–7.34 (comfort), 5.60–6.72 (resilience), 6.06–7.57 (risk avoidance), and 4.00–5.63 (achievement) for the total sample. Overall, MID estimates for WFIRS-P MID and CHIP-CE-PRF76 were slightly higher for adolescents than for children. Conclusion: This study estimated MIDs for these instruments using several methods. The observed convergence of the MID estimates increases confidence in their reliability and could assist clinicians and decision makers in deriving meaningful interpretations of observed changes in the WFIRS-P and CHIP-CE in clinical trials and practice.